Are K–12 Teachers Ready for E-learning? - Polat, Elif; Hopcan, Sinan; Yahşi, Ömer (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2022)
Readiness is important for the success of the e-learning process. The purpose of this study was twofold: to develop a scale to measure K–12 teachers’ e-learning readiness, and to examine their readiness to teach online. The participants were 3,295 K–12 teachers working in Izmir, Turkey. First EFA, then CFA-SEM was performed. Additionally, teachers’ e-readiness in terms of gender, years of service, school level, and daily device usage time were examined. Teachers are ready for e-learning considering their overall scores. A significant difference was found in favor of males in the “technical competence” factor and in favor of females in the “colleague, content, and pedagogical and ethical competence factors”. The readiness of younger teachers is generally higher. On a factor basis, there is only a significant difference in the factors of computer self-efficacy and student readiness according to educational level. As the use of devices increases, technology-related readiness increases. The readiness of teachers plays an important role in determining future strategies, measures, and interventions that need to be taken to advance e-learning.